Petrology: the study of igneous, sedimentary and metamorphic rocks by Loren A Raymond - Raymond, Loren A.; Raymond, Loren A. (Boston, McGraw Hill, 2002)
This text, designed for the middle-level undergraduate geology major, incorporates both fundamentals and information on recent advances in our understanding of igneous, sedimentary, and metamorphic rocks. It provides an overview of the field of petrology and a solid foundation for more advanced studies. For each class of rocks -- igneous, sedimentary, and metamorhic -- the author describes textures, structures, mineralogy, chemistry, and classification as a background to discussing representative occurrences and petrogenesis (rock origins).
Includes bibliographical references; Appendix A-C, 666-684p.; Glossary 685-707p.; Index 711-720p.
Keywords: Petrology; Geology